G476(P) Aminoacylase 1 deficiency, a clinical prospect. (25th October 2020) - KamarusJaman, N; Davison, J; Gissen, P; Krywawych, S
Abstract : Background: Aminoacylase-1 deficiency(OMIM 609924) is a rare form of inborn error of metabolism ( IEM) (Van Coster et al.2005 Sass et al. 2006) inherited by autosomal pattern characterized by increased urinary excretion of specific N-acetyl amino acids.Most patients demonstrate neurologic abnormalities such as intellectual disability, seizures, hypotonia, and motor delay. In this case series we describe four patients from diverse ethnic origins with slightly variable clinical phenotypes. Methods/Case Report: This retrospective case note review was conducted in a single metabolic centre at a tertiary care hospital in the UK. Clinical, biochemical, molecular genetic and neuro-imaging parameters were gathered from the clinical records, with a focus on the neurologic symptoms and signs. Results: Four patients were identified. Three were female in the age between 4–17 years at time of review and one male aged 7 years old. All of their urine organic acids showed elevated N acetyl amino acids consistent with disturbance in aminoacylase 1 activity. One patient also had biochemical, genetic confirmation of SCAD deficiency. A few patients confirmed molecular genetic mutation in the ACY1 Gene. 3 patients had brain MRI available, 1/3 was normal and 2/3 had non-specific imaging changes. Clinical neurological features included different phenotypes involving global developmental delay, seizures, hypotonia and speech delay. 1 patient had early infantile epileptic encephalopathy, 1 patient had neonatal hypotonia, and one patient had motor in co ordination, unsteadiness and speech delay thus describing phenotypic variability. Discussion: The study identified different phenotypic presentation in four unrelated patients widening the here-to described phenotypic spectrum. Urine organic acid analysis in patients with undiagnosed disorders with neurological phenotype it is useful in identifying a range of neurometabolic disorders, and subsequent enzymatic analysis or molecular genetics is important.